Factors Causing Pending BPJS Health Claims For Inpatient Services At Waled Regional Hospital In The Third Quarter Of 2025 - Tiara Atika Tri Kamilah; Yanto Haryanto; Bhakti Aryani; Fitria Dewi Rahmawati (International Journal of Health Engineering and Technology, 2026)
Pending BPJS Kesehatan claims remain a significant obstacle to hospital financing as they can disrupt cash flow and service continuity. This study aims to analyze the factors causing pending BPJS Kesehatan claims for inpatient services at Waled Regional Hospital in the third quarter of 2025. The study used a descriptive quantitative design with a retrospective cross-sectional approach. The population and sample consisted of 908 pending claim files using a total sampling technique. The research instrument was a checklist, while data analysis was conducted descriptively using frequency distribution and percentages. The results showed that the most common cause of pending claims was the coding aspect at 41.9%, followed by the medical aspect at 35.0% and the administrative aspect at 23.1%. In the administrative aspect, the most dominant problem was the mismatch of care classes. In the medical aspect, the main cause was neonatal asphyxia that did not meet the TKMKB criteria. In the coding aspect, the most common problem was inaccurate diagnosis codes or those that needed to be adjusted to clinical data based on verification BPJS. In conclusion, pending claims at Waled Regional Hospital are multidimensional and interrelated, thus requiring strengthening clinical documentation, coding accuracy, and integrated administrative verification.